Using biotechnology to improve growth rate and carcass composition in swine - Nelssen, Jim L. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Biotechnology has developed a number of compounds that partition nutrients away from fat tissue deposition and towards lean (muscle) tissue accretion in swine. Two compounds that have received considerable research attention are porcine somatotropin (growth hormone) and beta agonists. Somatotropin is a naturally occurring protein found in the blood of all mammals. Beta agonists are compounds commonly used in human medicine. Somatotropin and beta agonists can dramatically influence carcass leanness and ultimately pork product quality. Research has shown that porcine somatotropin can increase daily gains up to 19%, improve feed efficiency up to 28%, and reduce backfat thickness up to 33%. Research is underway to determine the effects of such compounds on nutrient requirements and reproduction in swine. Provided economic and safety requirements are met, somatotropin and/or beta agonist could revolutionize the future of the swine industry. These compounds are currently not available to the swine industry, except for research purposes.
Keywords: Swine; Biotechnology; Growth rate; Carcass composition